Loss of JAM‐C leads to impaired esophageal innervations and megaesophagus in mice. Issue 7 (30th June 2015) - Ye, M.; Zhang, Q.; Xu, X.; Zhang, Q.; Ge, Y.; Geng, P.; Yan, J.; Luo, L.; Sun, Y.; Liang, X.
Summary: Megaesophagus is a disease where peristalsis fails to occur properly and esophagus is enlarged. The etiology and mechanism of megaesophagus are not well understood. In this study, we reported that junctional adhesion molecule C (JAM‐C) knockout mice on a C57/B6 background developed progressive megaesophagus from embryonic day (E) 15.5 onward with complete penetrance. JAM‐C knockout mice exhibited a significant reduction in the number of nerve fibers/ganglia in the wall of the esophagus. However, histological analysis revealed that the esophageal wall thickness and structure of JAM‐C knockout mice at embryonic stages and young adult were comparable to that of control littermates. Thus, megaesophagus observed in JAM‐C knockout mice could be attributed, at least in part, to impaired esophageal innervations. Our data suggest JAM‐C as a potential candidate gene for human megaesophagus, and JAM‐C knockout mice might serve as a model for the study of human megaesophagus.